Evaluasi Program SMP Standar Nasional Berdasarkan Standar Nasional Pendidikan - Ida Kintamani DH (Jurnal Pendidikan dan Kebudayaan, 2011)
The purpose of this study was to evaluate the national standard of junior secondary school (JSS) program based on the level of achievement of Educational National Standards (ENS). The method used was a survey with a population of all the national standards of JSS, while the sampling method used was simple random sampling with a descriptive analysis technique. The results showed that the samples at 91.3 percent is a public JSS, and the remainder in private JSS. The schools vary from 250 to 1250 children. Of the eight ENSs, only seven ENSs that can be analyzed, while the financing could not be analyzed he data were not accurate. Of the seven ENSs, the maximum value should be obtained at 289, but actually the highest score is only 241 (83.39%) and lowest value of 170 (58.82%). Of the 7 ENSs, the highest achievement of Standard Process for 32 schools (72.73%) and lowest Graduates Competency Standards for the 22 schools (50.0%). When the average value of 208 ENSs have been achieved then assumed that only 23 schools (52.27%) who have reached the ENS, while 21 schools (47.73%), others are not achieved. Thus, it can be said that the 7 ENSs reached more than half. Therefore, competency standards lowest ‘needs to be achieved so that schools can improve attainment NSS value. For financing standard should take its own research.